Humoral response to heterologous prime‐booster vaccination in heart transplant recipients aged 18–70 years primed with a viral vector SARS‐CoV‐2 vaccine. Issue 6 (23rd August 2022) - Tanner, Richard; Starr, Neasa; Perez‐Garcia, Carlos Nicolas; Chan, Grace; Dempsey, Eimear; Heffernan, Emma; Lynch, Breda; Hannan, Margaret M; Joyce, Emer
Abstract: Solid organ transplant recipients have demonstrated a blunted immune response to standard 2‐dose vaccination against SARS‐CoV‐2. This study sought to determine the humoral response to heterologous booster vaccination (viral vector vaccine dose 1 and 2 + mRNA booster). Heart transplant recipients, aged 18 to 70 years of age who initially received two doses of the viral vector ChAdOx1 nCoV‐19 vaccine followed by a BNT162b2 mRNA booster were recruited. A detectable antibody response in the absence of prior SARS‐CoV‐2 was the primary outcome measured. This was defined as an anti‐spike titre of ≥0.8 U/mL on the Elecsys anti‐SARS‐CoV‐2 S immunoassay. A total of 80 heart transplant patients (mean age 49 ± 13 years, 28% female) were included. Blood samples were drawn at a median of 30 (IQR 28‐33) days after the BNT162b2 mRNA booster. The frequency of a detectable antibody response increased from 37.5% ( n = 30) after dose 2 to 56% ( n = 45) post dose 3 ( p < 0.001). A non‐detectable antibody response was significantly more common in recipients with a shorter time interval from transplantation ( p < 0.001), lower likelihood of cardiac allograft vasculopathy (p = 0.003) and in those prescribed a triple versus dual immunosuppressant regime ( p = 0.009) and a tacrolimus versus cyclosporine basedregimen ( p = 0.007). Despite heterologous prime‐booster vaccination 44% of this vulnerable population ultimately continue to have no detectable antibodies. Abstract : Graphical abstract :